ASSESSMENT ON DATA LEAKAGE PROTECTION FOR CHIEF GOVERMENT SECURITY OFFICE - Kumarendren Rajendran, 1980-, author; Nurulhuda Firdaus Mohd. Azmi, Dr., supervisor; Sekolah Informatiks Termaju (Kuala Lumpur : Universiti Teknologi Malaysia, 2017)
Thesis (Sarjana Sains (Jaminan Maklumat)) - Universiti Teknologi Malaysia, 2017